An asymmetric-square-wave voltage injection method for online inductance identification of PMSM under sensorless control - Yang Ge; Weizhang Song (Energy Reports, 2023)
In this paper, an online inductance identification method for PMSM, which is embedded into the flux-estimation-based sensorless control, is proposed. By injecting a periodic voltage where a larger negative voltage lasts one switching cycle, and a smaller positive voltage lasts several switching cycles, the extra voltage equation is established. Then, the q-axis current can be decomposed to an asymmetric triangular wave component and a low frequency component. Using the triangular wave current and the voltage equation, an inductance identification algorithm is designed. Since the injected positive voltage can be smaller, this method overcomes the difficulty that the symmetric square wave voltage cannot be injected at high-speed range, thus expanding the application of the inductance identification. And since the triangular wave current can be accurately extracted, the interference caused by back-EMF is eliminated. The simulation results demonstrate the effectiveness of the method.